Dampak Bullying Terhadap Perilaku Remaja; Studi Kasus pada Pelajar SMA Negri Palembang - Ira Permata (Universitas Muhammadiyah Sumatera Utara, 2022)
This study discusses the impact of bullying on adolescent behavior, where bullying itself is a hostile act carried out by one person or group of people with the aim of scaring or hurting others. This study aims to obtain a clear and in-depth picture of the impact of bullying on student behavior at SMA Negeri Palembang. This research was conducted using a qualitative case study approach, which seeks to describe and understand how the impact of bullying on adolescent behavior and how schools deal with the impact of bullying that occurs in the school environment. Data collection techniques were carried out by interview, observation. The results of the study indicate the impact of bullying on the behavior of students who are victims of bullying including; some victims feel afraid, feel inferior and some even feel uncomfortable, victims feel intimidated so that it makes them feel that school is not a fun place anymore, it becomes a scary place. A comprehensive policy is needed in schools, a policy that involves components from teachers to students, from school principals to parents of students, collaboration between teachers, parents and the community.Keywords: Bullying, Adolescent Behavior, School Violence